59. Evaluation of Drug-Bug Mismatch Alerts and Their Value in an Antimicrobial Stewardship Program - Whittaker, Cristen A (Open Forum Infect Dis, 2020)
BACKGROUND: Antimicrobial stewardship is a priority for hospitals and utilizing generated reports can enhance stewardship activities. At our institution, a software program was used to help optimize antimicrobial therapy by providing a drug-bug mismatch (DBM) alert which identifies patients with culture susceptibilities not covered by their current antimicrobial therapy. The purpose of this study was to evaluate the utility of this alert feature and determine whether or not an intervention was needed for patients identified. METHODS: From August 2019 to March 2020 the DBM alerts were reviewed by a pharmacist and interventions pursued when appropriate. Data collection included the patient’s culture results and source, indication for current antibiotics, and potential for intervention. Alerts were stratified into different groups based on the type of culture, including urine, blood, sputum, bone or bodily fluid, wound or tissues, and stool. Those mismatches not resulting in an intervention were categorized as a contamination, colonization, or inappropriate. This study was approved by the institutional review board. RESULTS: A total of 105 DBM alerts were analyzed from various sources, including 51 (47.6%) urine, 17 (16.2%) sputum, 16 (15.2%) wound or tissue, 14 (13.3%) blood, 6 (5.7%) bone or bodily fluid, and 1 stool culture. Overall, 48 of 105 (45.7%) of alerts resulted in an intervention. Urine and sputum culture alerts required interventions at the lowest rate with treatment interventions in 12 of 51 (23.5%) and 5 of 17 (29.4%) of those cases respectively. Blood culture alerts were the most successful as 9 of 14 (64.3%) alerts required an intervention. Alerts with wound or tissue cultures identified gaps in therapy as 9 of 16 (56.3%) cases required intervention. Colonization or contamination appeared to be the major cause of alerts that did not result in intervention. CONCLUSION: The DBM alert can be a beneficial tool for pharmacists participating in antimicrobial stewardship activities. However, the alerts had varying value depending on the culture source. The DBM alert can identify real-time patient issues regarding appropriate antimicrobial therapy. Further modifications to our process in utilizing this DBM report are warranted to enhance value and allocate time accordingly. DISCLOSURES: All Authors: No reported disclosures